Electrochemical Study of the Complexation of Quercetin with Lead (׀׀ ) ion in acidic media (Journal of the College of Basic Education, 2022)
Dietry flavonoids(Poly phenols) are important phytonutrient component widely distributed in plant foods , flavonoids have beneficial biological activities,such as antioxidant activity , flavonoids can chelate with metal ions , the interaction of lead(׀׀) ion with a poly hydroxylated flavonoids, the quercetin molecule,were investigated electrochemically in acidic media .The Differential Puls Polarographic Techanique was used to determine the kinetics parameters (Kס f,h , αn) using Meites- Israel method, also thermodynamic parameters such as enthalpy change (∆H), free energy chang (∆G) , entropy change(∆S) of Pb+2 – complexes with Quercetin at (293- 313k) . The(Kסf,h, αn)values for the kinetics of the electrode processes show that the electrode processes were irreversible and diffusion controlled.